Penyuluhan dan Pedampingan Penyusunan Pengelolaan Keuangan Panti Asuhan "Darus - Shiddiqien NW" Mertak Paok, Desa Mekar Bersatu Kecamatan Batukliang Kabupaten Lombok Tengah - Endar Pituringsih; Rr Titiek Herwanti; Lilik Handajani (Jurnal Gema Ngabdi, 2020)
The counseling and training activities on the preparation of financial management at the DarusShiddiqien NW Mertak Paok Reformatory in Central Lombok Regency aim to provide understanding and training to orphanage administrators in Central Lombok Regency. In addition, this training was conducted to provide knowledge to orphanage administrators about the importance of making financial reports, so that funds from donors can be managed properly. In the end, this activity is expected to produce human resources capable of making bookkeeping and financial management. This training activity will be aimed at administrators of the DarusShiddiqien NW Mertak Paok Islamic Boarding School in Central Lombok Regency. The implementation of the activity is carried out with the approach of presenting material relevant to the needs of the orphanage administrators according to PSAK 45. Another hope of this activity can be a means of carrying out community service activities, in particular providing counseling and training in preparing financial reports.